2017
DOI: 10.1159/000464328
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin as a Potential Early Predictive Factor in Metastatic Non-Small Cell Lung Cancer Patients Treated with Nivolumab

Abstract: Background/Aims: Prolactin (PRL) is a peptide hormone and several studies have demonstrated its role as a cytokine in human T cell-mediated immunity. We are unaware if PRL is a positive or negative immunomodulator, but its effects on the regulation of T cells could inhibit the antitumor activity elicited by nivolumab (NIVO). We aimed to assess whether the occurrence of hyperprolactinemia in metastatic non-small cell lung cancer (mNSCLC) patients treated with NIVO is associated with poor clinical outcomes. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Peripheral cytokines reflect status of tumor immune microenvironment and response to anti-PD-1/PD-L1 treatment [ 93 ]. Prolactin (PRL) participates in maturation and activation of immunity while high PRL inhibits immune response by IL-10 [ 105 ]. Adaptive hyperprolactinemia associates with poor response during nivolumab treatment and patients with stable concentration of PRL exhibit significant higher response rate ( p = 0.004) [ 105 ].…”
Section: Biomarkers In Peripheral Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral cytokines reflect status of tumor immune microenvironment and response to anti-PD-1/PD-L1 treatment [ 93 ]. Prolactin (PRL) participates in maturation and activation of immunity while high PRL inhibits immune response by IL-10 [ 105 ]. Adaptive hyperprolactinemia associates with poor response during nivolumab treatment and patients with stable concentration of PRL exhibit significant higher response rate ( p = 0.004) [ 105 ].…”
Section: Biomarkers In Peripheral Bloodmentioning
confidence: 99%
“…Prolactin (PRL) participates in maturation and activation of immunity while high PRL inhibits immune response by IL-10 [ 105 ]. Adaptive hyperprolactinemia associates with poor response during nivolumab treatment and patients with stable concentration of PRL exhibit significant higher response rate ( p = 0.004) [ 105 ]. Moreover, a phase 2 study revealed that pretreatment high level of IFN-γ, IL-6, and IL-10 in peripheral blood were relevant to increased objective response rate in melanoma patients receiving nivolumab [ 106 ].…”
Section: Biomarkers In Peripheral Bloodmentioning
confidence: 99%
“…Future research will also continue to explore other biomarkers routinely collected in the clinic that may predict response to ICI therapy. Biological plausibility and pilot investigations indicate that performance status, age, concomitant therapy (particularly high-dose corticosteroids), diversity of gut microbiome, prolactin, autoimmune diseases status, human leucocyte antigen class, DNA mismatch repair complex (MMR complex), tumour characteristics (size, location of metastases) and the level of tumour infiltrating lymphocytes are potential markers that should be more thoroughly investigated in the future ( Friedman and Postow, 2016 ; Nishijima et al , 2016 ; Seliger, 2016 ; Topalian et al , 2016 ; Caponnetto et al , 2017 ; Wargo et al , 2017 ; Johnson et al , 2017 ).…”
Section: Future Perspectivementioning
confidence: 99%
“…The associations of PRL and development of various cancer has been evaluated in breast, prostate, colorectal, gynecological, and hepatocellular cancer ( Goffin, 2017 ). Only a few studies have examined the relationship between the PRL levels and lung cancer ( Caponnetto et al, 2017 ; Seder et al, 2017 ). PRL was introduced in a seven-analyte panel of lung cancer biomarkers for the first time and the panel was suggested useful to risk stratify cancer patients for early recurrence after resection of node-negative NSCLC less than 4 cm ( Seder et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%